A REVIEW ON THE ROLE OF AVARANA (OCCLUSION OF BODY CHANNELS) IN METABOLIC SYNDROME - S, *Priya; M A, Shajahan (International Journal of Ayurveda and Pharma Research, 2017)
In Ayurvedic classics, the diseases caused by Vatha are considered as very serious diseases (Mahagada). One of the two pathological processes for the vitiation of Vatha is Avarana. Avarana is the disturbed movement of Vatha due to obstruction by other factors in the body. In the present social scenario, majority of diseases of Vatha are the result of Avarana, but the pathogenesis related to Avarana is least explored. Metabolic syndrome is one such lifestyle disease comprised of obesity, hyperglycemia, hypertension, hyper triglyceridemia and low HDL level. Majority of the symptoms of different Avarana conditions can be identified in patients presenting with metabolic syndrome. The general treatment protocol for Avarana is pacification of Vatha along with cleansing of channels and treatment of encroaching Dosha. Since metabolic syndrome is a disease with Avarana as the main pathophysiology, the treatment proposed by Acharyas for Avarana will be useful in metabolic syndrome. Since the vitiation is predominantly of Kapha and Meda, the drugs pacifying Kapha and Meda, cleansing of the channels, strengthening the tissues and not vitiating Vatha will be beneficial. The drugs may also be disease specific, like Pramehahara and Medodoshahara. Tinospora cordifolia (Guduchi) and Commiphora mukul (Guggulu) may be effective in metabolic syndrome since they are satisfying the above properties. Serious disease will develop, if the Avarana pathology is left untreated as evident in coronary artery disease.